Primary pulmonary glomus tumour: a diagnostic challenge. Issue 2 (13th February 2020) - Singh, Vikram; Kumar, Vikas; Singh, Harkant; Kakkar, Nandita
Abstract : Glomus tumour is uncommon benign tumour, which derives from the glomus cells present around arteriovenous anastomosis. These tumours are found most commonly in the deep dermis of the extremities. Primary pulmonary glomus tumour is extremely rare and often misdiagnosed. Knowledge about the existence of glomus tumour in the lung, its classic histomorphology and judicious use of immunohistochemistry can help us in clinching the correct diagnosis.